Optimization of Combustion Chamber Geometry for Reducing NOx Emissions in a Diesel Engine Fueled with B20 Biodiesel Blend - Rahmad Rahmad (PT Inovasi Pratama Internasional, 2026)
The adoption of B20 biodiesel blends in Indonesia’s diesel fleet is a strategic measure to reduce reliance on fossil fuels, yet it often elevates nitrogen oxide (NOx) emissions due to the fuel-bound oxygen and altered combustion phasing. This study presents a comprehensive numerical and experimental investigation aimed at optimizing the combustion chamber geometry of a 2.5 L turbocharged direct-injection diesel engine to mitigate NOx formation while maintaining engine performance with B20. A parametric design of experiments incorporating bowl diameter, bowl depth, squish clearance, and re-entrant ratio was constructed using a central composite design. Three-dimensional computational fluid dynamics simulations, validated by in-cylinder pressure and emission measurements, were performed for 30 distinct piston bowl configurations. Response surface methodology and a multi-objective genetic algorithm were employed to minimize NOx and soot emissions while limiting fuel consumption penalty. The optimal geometry—characterized by an enlarged bowl diameter (53.2 mm), a shallower bowl depth (17.8 mm), a reduced squish height (1.1 mm), and a mild re-entrant profile (ratio 0.72)—achieved a 34.2% reduction in NOx (from 4.82 to 3.17 g/kWh) compared to the baseline piston, with a moderate soot increase from 9.8 to 12.3 mg/kWh and a specific fuel consumption rise of only 1.4%. The improvement is primarily attributed to enhanced premixed combustion, lower peak temperatures, and a more homogeneous equivalence ratio distribution. The results confirm that tailored piston bowl optimization is a viable, cost-effective pathway for NOx compliance in B20-fuelled engines under Indonesian operating conditions